Protecting the fibular free flap during break in surgery: a technique - Daniel Dilworth; John Hanratty (Advances in Oral and Maxillofacial Surgery, 2025)
The use of fibular free flaps has become widespread in the reconstruction of large bony defects in the trauma and head and neck cancer patient with a high success rate. These surgeries can take a prolonged period of time, and oftentimes a break in surgery may be necessary, at which point the free flap may be vulnerable to iatrogenic damage. In this short communication, we describe a technique we regularly use at such an interval to protect the fibular free flap following soft tissue dissection and osteotomy but prior to its ligation and transfer up to the head for anastomosis, with the aim of minimising the risk of undue force being applied to the flap or any kinking or occluding of the pedicle.